Urgensi dan Visibilitas Konsolidasi Kajian MNCs dan Kajian INGOs dalam Studi Hubungan Internasional Dewasa Ini - Yunus, Mochamad; Susanto, Joko; Muttaqien, M (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2018)
This article tries to answer how the studies of MNCs-INGOs consolidated in the discipline of international relations. By using library research method and qualitative data analysis, it is found that the studies of MNCs-INGOs are possible and urgent to be developed in the international relations discipline. The importance of this study based on the fact that both MNCs and INGOs have developed as private transnational actors massively. The possibility to be independent study of IR is provided by the discource of internationalism. Moreover, if the comprehensive research is conducted it can be understood the transformation of not just only in the level of discource of the internationalism, but also on the exploration of the strategy and the governance of the MNCs-INGOs globally.